Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
- one /(two *x - one)^(three / two) = zero
minus 1 divide by (2 multiply by x minus 1) to the power of (3 divide by 2) equally 0
minus one divide by (two multiply by x minus one) to the power of (three divide by two) equally zero
-1/(2*x - 1)(3/2) = 0
-1/2*x - 13/2 = 0
-1/(2x - 1)^(3/2) = 0
-1/(2x - 1)(3/2) = 0
-1/2x - 13/2 = 0
-1/2x - 1^3/2 = 0
-1 divide by (2*x - 1)^(3 divide by 2) = 0
Similar expressions
1/(2*x - 1)^(3/2) = 0
-1/(2*x + 1)^(3/2) = 0
-1/(2*x - 1)^(3/2) = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]